Treatment of Dentine Hypersensitivity by Diode Laser: A Clinical Study - Romeo Umberto; Russo Claudia; Palaia Gaspare; Tenore Gianluca; Del Vecchio Alessandro (International Journal of Dentistry)
Introduction. Dentine hypersensitivity (DH) is characterized by pain after stimuli that usually provoke no symptoms. This study compared the effectiveness of GaAlAs diode laser alone and with topical sodium fluoride gel (NaF). Materials and Methods. The study was conducted on 10 patients (8 F/2 M, age 25–60) and 115 teeth with DH assessed by air and tactile stimuli measured by Numeric Rating Scale (NRS). Teeth were randomly divided into G1 (34 teeth) treated by 1.25% NaF; G2 (33 teeth) lased at 0.5 W PW (T on 100 m and T off 100 ms), fluence 62.2 J/cm2 in defocused mode with a 320 μ fiber. Each tooth received three 1′ applications; G3 (48 teeth) received NaF gel plus laser at same G2 parameters. NRS was checked at each control. Results. Significant pain reduction was showed. The NRS reduction percentages were calculated, and there was a concrete decrease of DH above all in G3 than G2 and G1. Conclusion. Diode laser is a useful device for DH treatment if used alone and mainly if used with NaF gel.